In Situ Neutralization and Detoxification of LPS to Attenuate Hyperinflammation - Xiaoyu Li; Shaoqi Qu; Xiangbin Song; Congming Wu; Jianzhong Shen; Kui Zhu (Advanced Science, 2023)
Abstract Hyperinflammation elicited by lipopolysaccharide (LPS) that derives from multidrug‐resistant Gram‐negative pathogens, leads to a sharp increase in mortality globally. However, monotherapies aiming to neutralize LPS often fail to improve the prognosis. Here, an all‐in‐one drug delivery strategy equipped with bactericidal activity, LPS neutralization, and detoxification is shown to recognize, kill pathogens, and attenuate hyperinflammation by abolishing the activation of LPS‐triggered acute inflammatory responses. First, bactericidal colistin results in rapid bacterial killing, and the released LPS is subsequently sequestered. The neutralized LPS is further cleared by acyloxyacyl hydrolase to remove secondary fatty chains and detoxify LPS in situ. Last, such a system shows high efficacy in two mouse infection models challenged with Pseudomonas aeruginosa. This approach integrates direct antibacterial activity with in situ LPS neutralizing and detoxifying properties, shedding light on the development of alternative interventions to treat sepsis‐associated infections.